Capitalising the farm family entrepreneur: negotiating private equity partnerships in Australia. Issue 4 (2nd October 2019) - Langford, Alexandra
ABSTRACT: Research on the financialisation of land and agribusiness has highlighted major shifts in agri-food systems globally. Yet these accounts tend to focus on the activities of financial actors, and few take seriously the role of farmers in negotiating investments in land and agribusiness. Farmers in the global North may be well placed to benefit from partnerships with financial investors, although little is known about the way that such partnerships are formed. Australian studies of farmer agency have been productive in examining farm family entrepreneurs and globally engaged farmers who work beyond the farm gate to organise supply chains. This paper adds to these studies by providing insights about a capitalising farm family entrepreneur, who successfully negotiated and entered into a direct equity partnership with a large foreign pension fund. Several observations are significant: the exceptional skill, time and expense required to negotiate these partnerships; the role of consultants and non-human actors in structuring them; and the spatially- and temporally divergent farm development practices that are enabled by a shift from debt to equity financing. These observations are indicative of a new adaptive strategy of family farmers to shifting financial landscapes and of emergent family, corporate, and financial farm hybridity.